Tinjauan Yuridis Aspek Hukum Pidana dalam Pengadaan Barang/Jasa Pemerintah Untuk Menjamin Akuntabilitas dan Transparansi Pengelolaan Keuangan Negara - Boby Ali Azhari; Samian Samian; Sarwono Hardjomuljadi (Jurnal Impresi Indonesia, 2026)
Public procurement in Indonesia plays a pivotal role in supporting national development. However, this sector remains susceptible to abuse of authority and corrupt practices that result in significant state financial losses. This research aims to analyze the application of criminal law and other relevant legal aspects in addressing irregularities within the procurement of goods and services. The methodology employed is normative legal research, utilizing a normative-juridical approach to examine prevailing laws and regulations. Furthermore, this study examines criminal elements that are prone to occur throughout various stages of public procurement, which currently utilizes an electronic procurement system as a solution to enhance transparency and efficiency. The research findings indicate that although electronic procurement systems improve accountability and transparency, challenges regarding infrastructure and human resource capacity remain primary obstacles to implementation. Criminal law aspects represent the most vulnerable legal dimension in public procurement; nevertheless, other legal aspects, such as administrative and civil law, cannot be disregarded. Ideally, the principle of ultimum remedium should be applied in circumstances where administrative or civil errors occur in the absence of malicious intent (mens rea). This study concludes that concerted efforts are required to strengthen the existing legal system, enhance the integrity of procurement officials, and involve the public in oversight processes. Through these measures, public procurement can operate more efficiently, remain free from corruption, and provide maximum benefits for national development.